THE SIGNIFICANCE OF POLITICAL STABILITY IN RURAL DEVELOPMENT AGENDA IN MATUNGGONG, SABAH - Romzi Ationg,; Mohd. Sohaimi Esa,; Irma Wani Othman,; Saifulazry Mokhtar, (Journal of Islamic, Social, Economics and Development, 2021)
Many suggests that the sub-district of Kudat which is also part of the Kota Maruduparliamentary constituency namely Matunggong in Sabah have been the area generallyaffected by poverty. Some even portrays Matunggong as an area in which the agenda of ruraldevelopment have been slow paced due to numbers of factors. It includes politicaldevelopment there which characterises by the propensity of political leadership changesduring elections because of conflicts or rampant competition between various political partiesas well as rivalry within the party. Having said that, however, the linkage between politicaldevelopment and specifically political stability, and the slow paced of rural development inMatunggong, Sabah, Malaysia has never been discussed systematically through the lens ofacademic. By applying a qualitative approach through the examination of informationgathered from various sources such as books, journals and media reports as well as interviewwith selected respondents, the paper presents a discussion on the the significance of politicalstability in rural development agenda in Matunggong of Sabah, Malaysia. The findings areexpected to contribute in the systematic understanding of linkages between political stabilityand rural development agenda, thus provides fundamental information on the way the ruralarea should be developed by the development agencies and specifically the political leaders.